Exploring Pre-Service Mathematics Teachers' Reasoning Skills in Solving Route Travel Problems: A Real-Life Application of Numeracy - Winarni, Sri; Kamid, Kamid; Marzal, Jefri; Asrial, Asrial (FKIP Universitas Lampung, 2024)
This research highlights the importance of numeracy as one of the indicators in assessing a country's progress. Numeracy bridges mathematical theory with practical application and can be used in everyday decision-making, such as financial decisions, health literacy, and risk assessment. However, the Minimum Competency Assessment results show that more than 50% of students still need to be in the low numeracy competency category. This research aims to explore the mathematical reasoning processes of pre-service mathematics teachers in solving travel route problems to understand their analytical skills. This research uses a qualitative descriptive approach with data collected from 30 fifth-semester mathematics education students at the University of Jambi. Data were obtained through numeracy tests, observations, and semi-structured interviews, allowing in-depth analysis of the participants' mathematical reasoning processes in solving contextual problems. Participants were asked to solve problems related to the context of travel routes, focusing on time and cost efficiency in choosing travel routes. The research results show that most participants can understand and model the problem, although there are differences in their approaches to solving it, ranging from very analytical to simple. Some participants initially misunderstood the problem, but after being given the opportunity for reflection, they were able to improve their understanding and the solutions produced. This research concludes that fostering mathematical reasoning in teacher training programs is crucial for improving numeracy skills. Sustained practice, reflection, and a structured problem-solving approach are necessary to help prospective teachers analyze and interpret mathematical problems more effectively. Keywords: mathematical reasoning, problem-solving, route travel, and pre-service mathematics teachers. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp712-727